2006 Sixth IEEE Conference on Nanotechnology 2006
DOI: 10.1109/nano.2006.247810
|View full text |Cite
|
Sign up to set email alerts
|

A Potentiometric Sensor System with Integrated Circuitry for in situ Environmental Monitoring

Abstract: applications.~~~~~~~~m icroelectrode sensor device that monitors the external Keyord -pteniomtri, snso, itegate, niseenvironmiental conditions. These electrodes produce a Keywrds potntioetri, snsor intgrae4 nisevoltage signal and pass it on to the second component, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A voltage follower circuit topology is generally used to provide a high-impedance interface. Potentiometric circuit examples can be found in [ 42 , 43 , 44 ]. Because the circuits for potentiometric sensors are relatively simple and not as commonly used in recent biosensors, this paper will focus on circuits for amperometric and impedimetric biosensors that are currently receiving much attention.…”
Section: Cmos Instrumentation For Amperometric and Impedimetric Bimentioning
confidence: 99%
“…A voltage follower circuit topology is generally used to provide a high-impedance interface. Potentiometric circuit examples can be found in [ 42 , 43 , 44 ]. Because the circuits for potentiometric sensors are relatively simple and not as commonly used in recent biosensors, this paper will focus on circuits for amperometric and impedimetric biosensors that are currently receiving much attention.…”
Section: Cmos Instrumentation For Amperometric and Impedimetric Bimentioning
confidence: 99%
“…In [37], it is found that, for any time measurement, u trigger is inversely proportional to the value of the voltage slope in the measurement pin when this voltage reaches the value V TL . From (11) it can be deduced that u trigger has the same form in all time measurements…”
Section: Errors Uncertainty and Resolutionmentioning
confidence: 99%
“…They are used, in the case of DCS, for measuring linear displacement and pressure differences [6], and for determining angular position [7,8] and acceleration [9,10]. DRSs are used in applications such as environmental monitoring [11], speed measurement [12], to sense linear or angular position displacement [13], and in rehabilitation devices [14]. These sensors also have inherent benefits, such as canceling the effects of temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…A voltage follower circuit is generally used to (1) provide a high impedance interface, so the output signal can be isolated from the source signal effectively. In addition, the instrumentation amplifier is characterized by high noise elimination capability and the high common mode rejection ratio (CMRR) which is generally >80 dB [56]. Potentiometry requires the input bias of the measurement circuit to be very low to reduce the measurement error to less than 1%.…”
Section: Potentiometric Protein Detectionmentioning
confidence: 99%